Identification and Toxicity Profiling of Column Fractions of Ethanol Leaf Extract of Ziziphus mauritiana - Owolarafe, Tajudeen Alowonle; Kailani, Salawu (Biology, Medicine, & Natural Product Chemistry, 2023)
Different plants may contain varying amounts of phytochemicals and also different degrees of toxicity. This study aimed to evaluate the phytochemicals present in the most active column fraction of ethanol leaf extract of the Ziziphus mauritiana plant and their toxic effects using brine shrimp lethality assay and animal model. Crude ethanol extract was obtained by maceration while fraction was achieved using a column chromatography experiment. Toxicity was evaluated with brine shrimp lethality assay and albino rat’s models while characterization was achieved with liquid chromatography-mass spectrophotometry. Ziziphus mauritiana leaves revealed 42 fractions pooled into seven fractions. Fraction three (3) was the most toxic with the brine shrimp lethality assay of (31.48ug/ml) and its toxicological evaluation revealed an adverse effect on the hematological parameter, biochemical indices, and histo-architecture of the liver and kidney of the experimental model studied. LCMS analysis of the most toxic fraction revealed the presence of Antirrhinoside, Lucidumol A, Apigenin 7-glucuronide-4'-(6''-malonylglucoside), Dioscoreside C, Camellioside D, and others which have been reported for various pharmacological effects including adverse effects, The mode of toxicity may be synergistic, individual, or antagonistic which may explain the moderate toxicity observed in animal model. Administration of these fractions may lead to toxicity despite their potential.